Peran Mahasiswa Fakultas Syariah Dan Hukum UINSU Dalam Melaksanakan Bantuan Hukum Secara Non Litigasi - Panjaitan, Budi Sastra; Lubis, Syofiaty; Ghania, Sophia (Universitas Medan Area, 2024)
Legal aid is one tool in efforts to achieve justice for the poor in Indonesia. Implementing legal aid is not only limited to the advocate profession but also legal professionals, lecturers, and law students. The involvement of UINSU Sharia and Law Faculty Students in Implementing Non-Litigation Legal Aid is not limited to just the demands of the legal aid law but is also an implementation of religious commands to always do good and prevent evil. In the academic aspect, the implementation of non-litigation legal assistance carried out by UINSU Faculty of Sharia and Law students is an experience in itself to test the theoretical knowledge gained in class with law enforcement practice in the field. This research is included in the qualitative research category. The research results concluded that even though it is still relatively limited, UINSU Faculty of Sharia and Law students have played a role in implementing non-litigation legal assistance. Barriers experienced by UINSU Faculty of Sharia and Law students in legal aid activities include lack of support, lack of student awareness of the social environment, lack of campus facilities and infrastructure, lack of funding for legal aid, quite busy study time, lack of self-confidence, lack of public understanding regarding legal aid as a right and public doubts regarding the status of students who can carry out non-litigation legal aid.